Anti-degradation automobile exhaust purification three-way catalyst and preparation method thereof

By designing a multi-layer coating structure in the catalyst, using the combination of magnesium-aluminum composite oxide, cerium-zirconium composite oxide and precious metal, combined with the multi-layer distribution control of lanthanum salt, the problems of high amount of precious metals used and poor high temperature stability of existing catalysts are solved, and a three-way catalyst with efficient ignition and high durability are achieved.

CN119633817APending Publication Date: 2025-03-18WUXI WEIFU ENVIRONMENT PROTECTION CATALYST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411827059.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When existing catalysts meet the low emission limit and high durability requirements of National VI (b), high amount of precious metals leads to an increase in costs, and the anchoring is unstable under high temperature conditions and low ignition efficiency.

Method used

Using a three-way catalyst, the coating consists of a lower coating, an intermediate coating and an upper coating arranged in sequence from bottom to top. The lower coating contains magnesium-aluminum composite oxide, the first cerium-zirconium composite oxide and precious metal Pd, the intermediate coating contains lanthanum rhenium composite oxide, the second cerium-zirconium composite oxide and precious metal Rh. The upper coating is a lanthanum coating formed by the lanthanum salt solution. Through strong interaction and multi-layer distribution control of lanthanum salt, the high temperature stability and sintering resistance of the catalyst are improved.

Benefits of technology

The catalyst is efficiently ignited and has high temperature stability, which reduces the amount of precious metals, improves the durability and water resistance and sulfur resistance of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005184581350000071
    Figure BDA0005184581350000071
Patent Text Reader

Abstract

The invention provides an anti-degradation automobile exhaust purification three-way catalyst and a preparation method thereof.The three-way catalyst comprises a carrier and a coating coated on the carrier, and the coating comprises a lower coating, a middle coating and an upper coating which are sequentially arranged on the carrier from bottom to top; the lower coating comprises a magnesium-aluminum composite oxide, a first cerium-zirconium composite oxide and precious metal Pd, the middle coating comprises a lanthanum-aluminum composite oxide, a second cerium-zirconium composite oxide and precious metal Rh, and the upper coating is a lanthanum coating formed by dipping a lanthanum salt solution. According to the catalyst disclosed by the invention, the noble metal Pd and the MgO-Al2O3 material are combined, so that the Pd is effectively anchored on the carrier more stably under a high-temperature condition, the Pd is distributed more uniformly, the ignition of the catalyst can be effectively accelerated, and meanwhile, the high-temperature stability of the catalyst is ensured; the outermost layer of the catalyst is impregnated with lanthanum salt to adjust multi-layer distribution control of La in the catalyst, and the anti-sintering performance of the catalyst is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a three-way catalyst for purifying anti-deterioration automobile exhaust and a preparation method thereof. Background Art

[0002] With the rapid development of the global automobile industry, automobile exhaust emissions have become one of the important sources of environmental pollution. In order to cope with increasingly stringent environmental regulations and improve air quality, the research and application of automobile exhaust catalysts is particularly important. As consumers' requirements for automobile environmental performance increase, the market demand for high-efficiency and high-durability exhaust catalysts continues to grow, which provides a broad market space for the research and development and application of anti-degradation automobile exhaust catalysts.

[0003] With the rapid development of electric vehicles, hybrid vehicles are becoming more and more popular in the market. The pollutant emissions of hybrid vehicles are mainly concentrated in cold start and high-load hot start conditions, and it is necessary to develop new catalyst technologies with faster ignition and higher conversion efficiency; therefore, in order to meet the low emission limits and high durability requirements of National VI (b), the use of existing catalyst technology requires a higher amount of precious metals to ensure low-temperature ignition and activity after aging, which leads to a significant increase in costs; therefore, how to achieve a strong interaction between platinum group metals and coating materials during the catalyst preparation process while ensuring catalytic efficiency, achieve a high dispersion of platinum group metals, and at the same time ensure the anti-sintering ability of platinum group metals is particularly important and has become a key direction of current catalyst research and development. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies in the prior art and to provide a three-way catalyst for purifying automobile exhaust gas with resistance to degradation and a preparation method thereof. The catalyst has a high nitrogen oxide removal rate and has high water and sulfur resistance.

[0005] The technical solution adopted by the present invention is:

[0006] A three-way catalyst for purifying automobile exhaust gas that resists degradation, comprising a carrier and a coating coated on the carrier, wherein the coating comprises a lower coating, an intermediate coating and an upper coating arranged on the carrier in sequence from bottom to top, the lower coating comprises a magnesium-aluminum composite oxide, a first cerium-zirconium composite oxide and a precious metal Pd, the intermediate coating comprises a lanthanum-aluminum composite oxide, a second cerium-zirconium composite oxide and a precious metal Rh, and the upper coating is a lanthanum coating formed by immersing in a lanthanum salt solution.

[0007] Preferably, in the three-way catalyst for purifying automobile exhaust gas with resistance to degradation, the loading amount of the precious metal Pd in ​​the lower coating layer is 1 to 200 g / ft 3 The loading amount of the noble metal Rh in the intermediate coating is 0.1 to 30 g / ft 3 .

[0008] Preferably, in the three-way catalyst for purifying automobile exhaust gas with resistance to degradation, the magnesium-aluminum composite oxide comprises, by mass percentage, 1 wt% to 30 wt% of magnesium oxide and 70 wt% to 99 wt% of aluminum oxide.

[0009] Preferably, the three-way catalyst for purifying automobile exhaust gas with resistance to degradation, wherein, in terms of mass percentage, the first cerium-zirconium composite oxide and the second cerium-zirconium composite oxide both comprise 4wt% to 79wt% ZrO2, 20wt% to 95wt% CeO2 and 1wt% to 10wt% transition metal oxide, and the transition metal oxide is selected from La2O3, Y2O3, Pr6O 11 , one or more of Nd2O3.

[0010] Preferably, in the three-way catalyst for purifying automobile exhaust gas with resistance to degradation, the mass ratio of the magnesium-aluminum composite oxide to the first cerium-zirconium composite oxide is 1:10 to 10:1.

[0011] Preferably, in the three-way catalyst for purifying automobile exhaust gas with resistance to degradation, the lanthanum-aluminum composite oxide comprises, by mass percentage, 1 wt% to 10 wt% of lanthanum oxide and 90 wt% to 99 wt% of aluminum oxide.

[0012] Preferably, in the three-way catalyst for purifying automobile exhaust gas with resistance to degradation, the mass ratio of the lanthanum aluminum composite oxide to the second cerium zirconium composite oxide is 1:10 to 10:1.

[0013] The present invention also provides a method for preparing a three-way catalyst for purifying automobile exhaust gas with resistance to degradation, comprising the following steps:

[0014] (1) coating of the lower coating layer: weighing a magnesium aluminum composite oxide and a first cerium zirconium composite oxide in a mass ratio of 1:10 to 10:1, then adding the magnesium aluminum composite oxide and the first cerium zirconium composite oxide to deionized water and stirring them uniformly to obtain a first slurry, adding a precious metal Pd precursor solution dropwise to the first slurry, then stirring uniformly to obtain an undercoat slurry, then coating the undercoat slurry on a carrier at a coating amount of 50 to 200 g / L, and finally drying and calcining to obtain a first semi-finished product;

[0015] (2) coating of an intermediate coating: weighing a lanthanum aluminum composite oxide and a second cerium zirconium composite oxide in a mass ratio of 1:10 to 10:1, then adding the lanthanum aluminum composite oxide and the second cerium zirconium composite oxide to deionized water and stirring uniformly to obtain a second slurry, dropping a precursor solution of the precious metal Rh into the second slurry, stirring uniformly to obtain an intermediate coating slurry, and then coating the intermediate coating slurry on the semi-finished product obtained in step (1) at a coating amount of 50 to 200 g / L, and finally drying and calcining to obtain a second semi-finished product;

[0016] (3) Coating of the top coating: impregnate a certain amount of lanthanum salt solution from the air inlet end onto the second semi-finished product prepared in step (2), control the impregnation height to be 80% to 90% of the catalyst length, and finally dry and calcine to obtain a finished catalyst.

[0017] Preferably, in the method for preparing the three-way catalyst for purifying automobile exhaust gas with resistance to degradation, the drying temperatures in step (1), step (2) and step (3) are all 80-200°C, the drying time is all 0.1-10h, the calcination temperature is all 450-800°C, and the calcination time is all 1-8h.

[0018] Preferably, in the method for preparing the three-way catalyst for purifying automobile exhaust gas with resistance to degradation, the lanthanum salt in step (3) is selected from one or more of lanthanum nitrate, lanthanum acetate and lanthanum aminosulfonate, and the impregnation amount of the lanthanum salt solution is 0.1 to 10 g / L.

[0019] Advantages of the present invention:

[0020] The three-way catalyst for purifying automobile exhaust gas with resistance to degradation of the present invention and its preparation method include a carrier and a coating coated on the carrier, wherein the coating includes a lower coating, an intermediate coating and an upper coating arranged on the carrier in sequence from bottom to top. On the one hand, the catalyst is combined with precious metal Pd and MgO-Al2O3 material, and through the strong interaction between MgO-Al2O3 and Pd, Pd is effectively anchored on the carrier more stably under high temperature conditions, and Pd is more evenly distributed on the carrier, which can effectively accelerate the ignition of the catalyst and ensure the high-temperature stability of the catalyst; on the other hand, lanthanum salt is impregnated in the outermost layer of the catalyst to adjust the multi-layer distribution control of La in the catalyst, thereby further improving the anti-sintering performance of the catalyst. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with specific embodiments.

[0022] Example 1

[0023] A three-way catalyst for purifying automobile exhaust gas that resists degradation comprises a carrier and a coating coated on the carrier, wherein the coating comprises a lower coating, an intermediate coating and an upper coating arranged on the carrier in sequence from bottom to top, the lower coating comprises a magnesium-aluminum composite oxide, a first cerium-zirconium composite oxide and a precious metal Pd, the intermediate coating comprises a lanthanum-aluminum composite oxide, a second cerium-zirconium composite oxide and a precious metal Rh, and the upper coating is a lanthanum coating formed by immersing in a lanthanum salt solution.

[0024] The loading amount of precious metal Pd in ​​the lower coating is 168g / ft 3 The loading amount of the precious metal Rh in the intermediate coating is 13 g / ft 3 ; In terms of mass percentage, the magnesium-aluminum composite oxide includes magnesium oxide and aluminum oxide in a mass ratio of 7.5:42.5; the first cerium-zirconium composite oxide includes ZrO2, CeO2 and Nd2O3 in a mass ratio of 40:55:2, and the mass ratio of the magnesium-aluminum composite oxide to the cerium-zirconium composite oxide is 1:1; in terms of mass percentage, the lanthanum-aluminum composite oxide includes 3wt% of lanthanum oxide and 97wt% of aluminum oxide; the mass ratio of the lanthanum-aluminum composite oxide and the second cerium-zirconium composite oxide is 3:7, and the second cerium-zirconium composite oxide includes ZrO2, CeO2 and Y2O3 in a mass ratio of 20:70:5.

[0025] The preparation method of the three-way catalyst for purifying automobile exhaust gas with resistance to degradation in this embodiment comprises the following steps:

[0026] (1) Coating of the lower coating layer: 500 g of magnesium-aluminum composite oxide and 500 g of the first cerium-zirconium composite oxide were weighed in a mass ratio of 1:1, and then the magnesium-aluminum composite oxide and the first cerium-zirconium composite oxide were added to deionized water and stirred evenly to obtain a first slurry, 90 g of palladium nitrate solution (containing 9 g of Pd element) was added dropwise to the first slurry, and then stirred evenly to obtain an undercoat slurry, and then the undercoat slurry was coated on the carrier at a coating amount of 100 g / L, and finally dried and calcined to obtain a first semi-finished product, the drying temperature was 120° C., the drying time was 5 h, the calcination temperature was 550° C., and the calcination time was 2 h;

[0027] (2) Application of intermediate coating: 300 g of lanthanum aluminum composite oxide and 700 g of second cerium zirconium composite oxide were weighed in a mass ratio of 3:7, wherein the second cerium zirconium composite oxide comprises ZrO2, CeO2 and Y2O3 in a ratio of 20:70:5, and then the lanthanum aluminum composite oxide and the cerium zirconium composite oxide were added to deionized water and stirred to obtain a second slurry, 7 g of rhodium nitrate solution (containing 0.7 g of Rh element) was added dropwise to the second slurry, and stirred to obtain an intermediate coating slurry, and then the intermediate coating slurry was applied to the semi-finished product obtained in step (1) at a coating amount of 70 g / L, and finally dried and calcined to obtain a second semi-finished product, the drying temperature was 120°C, the drying time was 5 h, and the calcination temperature was 550°C, and the calcination time was 2 h;

[0028] (3) Coating of the top coating: impregnate 100 g of lanthanum nitrate solution (containing 0.3 g of La2O3) from the air inlet end onto the second semi-finished product prepared in step (2), control the impregnation height to be 85% of the catalyst length, and finally dry and calcine at a drying temperature of 120°C for 5 h and a calcination temperature of 550°C for 2 h to obtain a finished catalyst.

[0029] Example 2

[0030] A three-way catalyst for purifying automobile exhaust gas that resists degradation comprises a carrier and a coating coated on the carrier, wherein the coating comprises a lower coating, an intermediate coating and an upper coating arranged on the carrier in sequence from bottom to top, the lower coating comprises a magnesium-aluminum composite oxide, a first cerium-zirconium composite oxide and a precious metal Pd, the intermediate coating comprises a lanthanum-aluminum composite oxide, a second cerium-zirconium composite oxide and a precious metal Rh, and the upper coating is a lanthanum coating formed by immersing in a lanthanum salt solution.

[0031] The loading amount of precious metal Pd in ​​the lower coating is 93.3 g / ft 3 The loading amount of the precious metal Rh in the intermediate coating is 18.7 g / ft 3 The magnesium-aluminum composite oxide comprises magnesium oxide and aluminum oxide in a mass ratio of 7.5:42.5; the first cerium-zirconium composite oxide comprises ZrO2, CeO2 and Nd2O3 in a mass ratio of 30:65:2; the mass ratio of the magnesium-aluminum composite oxide and the cerium-zirconium composite oxide is 1:1; in terms of mass percentage, the lanthanum-aluminum composite oxide comprises 3wt% of lanthanum oxide and 97wt% of aluminum oxide; the mass ratio of the lanthanum-aluminum composite oxide and the second cerium-zirconium composite oxide is 3:7, and the second cerium-zirconium composite oxide comprises ZrO2, CeO2 and Y2O3 in a mass ratio of 20:70:5 3。

[0032] The preparation method of the three-way catalyst for purifying automobile exhaust gas with resistance to degradation in this embodiment comprises the following steps:

[0033] (1) Coating of the lower coating layer: 500 g of magnesium-aluminum composite oxide and 500 g of the first cerium-zirconium composite oxide were weighed in a mass ratio of 1:1, and then the magnesium-aluminum composite oxide and the first cerium-zirconium composite oxide were added to deionized water and stirred evenly to obtain a first slurry, 50 g of palladium nitrate solution (containing 5 g of Pd element) was added dropwise to the first slurry, and then stirred evenly to obtain an undercoat slurry, and then the undercoat slurry was coated on the carrier at a coating amount of 100 g / L, and finally dried and calcined to obtain a first semi-finished product, the drying temperature was 120° C., the drying time was 5 h, the calcination temperature was 550° C., and the calcination time was 2 h;

[0034] (2) Application of intermediate coating: 300 g of lanthanum aluminum composite oxide and 700 g of second cerium zirconium composite oxide were weighed in a mass ratio of 3:7, wherein the second cerium zirconium composite oxide comprises ZrO2, CeO2 and Y2O3 in a ratio of 20:70:5, and then the lanthanum aluminum composite oxide and the second cerium zirconium composite oxide were added to deionized water and stirred evenly to obtain a second slurry, 10 g of rhodium nitrate solution (containing 1 g of Rh element) was added dropwise to the second slurry, stirred evenly to obtain an intermediate coating slurry, and then the intermediate coating slurry was applied to the semi-finished product obtained in step (1) at a coating amount of 70 g / L, and finally dried and calcined to obtain a second semi-finished product, the drying temperature was 120°C, the drying time was 5 h, and the calcination temperature was 550°C, and the calcination time was 2 h;

[0035] (3) Coating of the top coating: impregnate 100 g of lanthanum acetate solution (containing 0.2 g of La2O3) from the air inlet end onto the second semi-finished product prepared in step (2), and control the impregnation height to be 85% of the catalyst length. Finally, dry and calcine at a drying temperature of 120°C for 5 h, a calcination temperature of 550°C for 2 h, and a finished catalyst.

[0036] Example 3

[0037] A three-way catalyst for purifying automobile exhaust gas that resists degradation comprises a carrier and a coating coated on the carrier, wherein the coating comprises a lower coating, an intermediate coating and an upper coating arranged on the carrier in sequence from bottom to top, the lower coating comprises a magnesium-aluminum composite oxide, a first cerium-zirconium composite oxide and a precious metal Pd, the intermediate coating comprises a lanthanum-aluminum composite oxide, a second cerium-zirconium composite oxide and a precious metal Rh, and the upper coating is a lanthanum coating formed by immersing in a lanthanum salt solution.

[0038] The loading amount of precious metal Pd in ​​the lower coating is 112 g / ft 3 The loading amount of the precious metal Rh in the intermediate coating is 18.7 g / ft 3The magnesium-aluminum composite oxide comprises magnesium oxide and aluminum oxide in a mass ratio of 5:45; the first cerium-zirconium composite oxide comprises ZrO2, CeO2 and Nd2O3 in a mass ratio of 30:65:2.

[0039] The mass ratio of the magnesium-aluminum composite oxide to the cerium-zirconium composite oxide is 1:1; in terms of mass percentage, the lanthanum-aluminum composite oxide includes 5wt% of lanthanum oxide and 95wt% of aluminum oxide; the mass ratio of the lanthanum-aluminum composite oxide to the second cerium-zirconium composite oxide is 3:7, and the second cerium-zirconium composite oxide includes ZrO2, CeO2 and Y2O3 in a mass ratio of 20:70:5.

[0040] The preparation method of the three-way catalyst for purifying automobile exhaust gas with resistance to degradation in this embodiment comprises the following steps:

[0041] (1) Coating of the lower coating layer: 500 g of magnesium-aluminum composite oxide and 500 g of the first cerium-zirconium composite oxide were weighed in a mass ratio of 1:1, and then the magnesium-aluminum composite oxide and the first cerium-zirconium composite oxide were added to deionized water and stirred evenly to obtain a first slurry, 60 g of palladium nitrate solution (containing 6 g of Pd element) was added dropwise to the first slurry, and then stirred evenly to obtain an undercoating slurry, and then the undercoating slurry was coated on the carrier at a coating amount of 100 g / L, and finally dried and calcined to obtain a first semi-finished product, the drying temperature was 120° C., the drying time was 5 h, the calcination temperature was 550° C., and the calcination time was 2 h;

[0042] (2) Application of intermediate coating: 300 g of lanthanum aluminum composite oxide and 700 g of second cerium zirconium composite oxide were weighed in a mass ratio of 3:7, wherein the second cerium zirconium composite oxide comprises ZrO2, CeO2 and Y2O3 in a ratio of 20:70:5, and then the lanthanum aluminum composite oxide and the second cerium zirconium composite oxide were added to deionized water and stirred evenly to obtain a second slurry, 10 g of rhodium nitrate solution (containing 1 g of Rh element) was added dropwise to the second slurry, stirred evenly to obtain an intermediate coating slurry, and then the intermediate coating slurry was applied to the semi-finished product obtained in step (1) at a coating amount of 70 g / L, and finally dried and calcined to obtain a second semi-finished product, the drying temperature was 120°C, the drying time was 5 h, and the calcination temperature was 550°C, and the calcination time was 2 h;

[0043] (3) Coating of the top coating: impregnate 100 g of lanthanum aminosulfonate solution (containing 0.3 g La2O3) from the air inlet end onto the second semi-finished product prepared in step (2), and control the impregnation height to be 85% of the catalyst length. Finally, dry and calcine at a drying temperature of 120°C for 5 h and a calcination temperature of 550°C for 2 h to obtain a finished catalyst.

[0044] Comparative Example 1

[0045] A three-way catalyst for purifying automobile exhaust gas with resistance to degradation comprises a carrier and a coating coated on the carrier, wherein the coating comprises a lower coating and an upper coating arranged on the carrier in sequence from bottom to top, the lower coating comprises a magnesium-aluminum composite oxide, a first cerium-zirconium composite oxide and a precious metal Pd, and the upper coating comprises a lanthanum-aluminum composite oxide, a second cerium-zirconium composite oxide and a precious metal Rh.

[0046] The loading amount of precious metal Pd in ​​the lower coating is 168g / ft 3 The loading amount of the precious metal Rh in the intermediate coating is 13 g / ft 3 ; The magnesium-aluminum composite oxide comprises magnesium oxide and aluminum oxide in a mass ratio of 7.5:42.5; the first cerium-zirconium composite oxide comprises ZrO2, CeO2 and Nd2O3 in a mass ratio of 40:55:2.

[0047] The mass ratio of the magnesium-aluminum composite oxide to the cerium-zirconium composite oxide is 1:1; in terms of mass percentage, the lanthanum-aluminum composite oxide includes 5wt% of lanthanum oxide and 95wt% of aluminum oxide; the mass ratio of the lanthanum-aluminum composite oxide to the second cerium-zirconium composite oxide is 3:7, and the second cerium-zirconium composite oxide includes ZrO2, CeO2 and Y2O in a mass ratio of 20:70:5 3。

[0048] The preparation method of the three-way catalyst for purifying automobile exhaust gas with resistance to degradation in this comparative example comprises the following steps:

[0049] (1) Coating of the lower coating layer: 500 g of magnesium-aluminum composite oxide and 500 g of the first cerium-zirconium composite oxide were weighed in a mass ratio of 1:1, and then the magnesium-aluminum composite oxide and the first cerium-zirconium composite oxide were added to deionized water and stirred evenly to obtain a first slurry, 90 g of palladium nitrate solution (containing 9 g of Pd element) was added dropwise to the first slurry, and then stirred evenly to obtain an undercoat slurry, and then the undercoat slurry was coated on the carrier at a coating amount of 100 g / L, and finally dried and calcined to obtain a first semi-finished product, the drying temperature was 120° C., the drying time was 5 h, the calcination temperature was 550° C., and the calcination time was 2 h;

[0050] (2) Application of top coating: 300 g of lanthanum aluminum composite oxide (La2O3:Al2O3=2.5:47.5) and 700 g of second cerium zirconium composite oxide were weighed in a mass ratio of 3:7, wherein the second cerium zirconium composite oxide comprises ZrO2, CeO2 and Y2O3 in a ratio of 20:70:5. Then, the lanthanum aluminum composite oxide and the cerium zirconium composite oxide were added into deionized water and stirred evenly to obtain a second slurry. 7 g of rhodium nitrate solution (containing 0.7 g of Rh element) was added dropwise into the second slurry and stirred evenly to obtain a top coating slurry. Then, the top coating slurry was applied to the semi-finished product obtained in step (1) at a coating amount of 70 g / L. Finally, the catalyst was dried and calcined to obtain a finished product. The drying temperature was 120°C and the drying time was 5 h. The calcination temperature was 550°C and the calcination time was 2 h.

[0051] Comparative Example 2

[0052] A three-way catalyst for purifying automobile exhaust gas that resists degradation comprises a carrier and a coating coated on the carrier, wherein the coating comprises a lower coating, an intermediate coating and an upper coating arranged on the carrier in sequence from bottom to top, wherein the lower coating comprises a lanthanum-aluminum composite oxide, a first cerium-zirconium composite oxide and a precious metal Pd, the intermediate coating comprises a lanthanum-aluminum composite oxide, a second cerium-zirconium composite oxide and a precious metal Rh, and the upper coating is a lanthanum coating formed by immersing in a lanthanum salt solution.

[0053] The loading amount of precious metal Pd in ​​the lower coating is 168g / ft 3 The loading amount of the precious metal Rh in the intermediate coating is 13 g / ft 3 The lanthanum aluminum composite oxide comprises magnesium oxide and aluminum oxide in a mass ratio of 1.5:48.5; the first cerium zirconium composite oxide comprises ZrO2, CeO2 and Nd2O3 in a mass ratio of 30:65:2; the mass ratio of the lanthanum aluminum composite oxide and the cerium zirconium composite oxide is 1:1; the mass ratio of the lanthanum aluminum composite oxide and the second cerium zirconium composite oxide is 3:7, and the second cerium zirconium composite oxide comprises ZrO2, CeO2 and Y2O3 in a mass ratio of 20:70:5 3。

[0054] The preparation method of the three-way catalyst for purifying automobile exhaust gas with resistance to degradation in this comparative example comprises the following steps:

[0055] (1) Coating of the lower coating layer: 500 g of lanthanum aluminum composite oxide and 500 g of the first cerium zirconium composite oxide were weighed in a mass ratio of 1:1, and then the magnesium aluminum composite oxide and the first cerium zirconium composite oxide were added to deionized water and stirred evenly to obtain a first slurry, 90 g of palladium nitrate solution (containing 9 g of Pd element) was added dropwise to the first slurry, and then stirred evenly to obtain an undercoat slurry, and then the undercoat slurry was coated on the carrier at a coating amount of 100 g / L, and finally dried and calcined to obtain a first semi-finished product, the drying temperature was 120° C., the drying time was 5 h, the calcination temperature was 550° C., and the calcination time was 2 h;

[0056] (2) Application of intermediate coating: 300 g of lanthanum aluminum composite oxide and 700 g of second cerium zirconium composite oxide were weighed in a mass ratio of 3:7, wherein the second cerium zirconium composite oxide included ZrO2, CeO2 and Y2O3 in a ratio of 20:70:5, and then the lanthanum aluminum composite oxide and the second cerium zirconium composite oxide were added to deionized water and stirred evenly to obtain a second slurry, 7 g of rhodium nitrate solution (containing 0.7 g of Rh element) was added dropwise to the second slurry, and stirred evenly to obtain an intermediate coating slurry, and then the intermediate coating slurry was applied to the semi-finished product obtained in step (1) at a coating amount of 70 g / L, and finally dried and calcined to obtain a second semi-finished product, the drying temperature was 120°C, the drying time was 5 h, and the calcination temperature was 550°C, and the calcination time was 2 h;

[0057] (3) Coating of the top coating: impregnate 100 g of lanthanum nitrate solution (containing 0.3 g of La2O3) from the air inlet end onto the second semi-finished product prepared in step (2), control the impregnation height to be 85% of the catalyst length, and finally dry and calcine at a drying temperature of 120°C for 5 h and a calcination temperature of 550°C for 2 h to obtain a finished catalyst.

[0058] Comparative Example 3

[0059] A three-way catalyst for purifying automobile exhaust gas with resistance to degradation comprises a carrier and a coating coated on the carrier, wherein the coating comprises a lower coating and an upper coating arranged on the carrier in sequence from bottom to top, the lower coating comprises a lanthanum-aluminum composite oxide, a first cerium-zirconium composite oxide and a precious metal Pd, and the upper coating comprises a lanthanum-aluminum composite oxide, a second cerium-zirconium composite oxide and a precious metal Rh.

[0060] The loading amount of precious metal Pd in ​​the lower coating is 168g / ft 3 The loading amount of the precious metal Rh in the intermediate coating is 18.6 g / ft 3The lanthanum-aluminum composite oxide comprises lanthanum oxide and aluminum oxide in a mass ratio of 1.5:48.5; the first cerium-zirconium composite oxide comprises ZrO2, CeO2 and Nd2O3 in a mass ratio of 30:65:2, and the mass ratio of the lanthanum-aluminum composite oxide to the cerium-zirconium composite oxide is 1:1; the mass ratio of the lanthanum-aluminum composite oxide and the second cerium-zirconium composite oxide is 3:7, and the second cerium-zirconium composite oxide comprises ZrO2, CeO2 and Y2O3 in a mass ratio of 20:70:5 3。

[0061] The preparation method of the three-way catalyst for purifying automobile exhaust gas with resistance to degradation in this comparative example comprises the following steps:

[0062] (1) Coating of the lower coating layer: 500 g of lanthanum aluminum composite oxide and 500 g of the first cerium zirconium composite oxide were weighed in a mass ratio of 1:1, and then the magnesium aluminum composite oxide and the first cerium zirconium composite oxide were added to deionized water and stirred evenly to obtain a first slurry, 90 g of palladium nitrate solution (containing 9 g of Pd element) was added dropwise to the first slurry, and then stirred evenly to obtain an undercoat slurry, and then the undercoat slurry was coated on the carrier at a coating amount of 100 g / L, and finally dried and calcined to obtain a first semi-finished product, the drying temperature was 120° C., the drying time was 5 h, the calcination temperature was 550° C., and the calcination time was 2 h;

[0063] (2) Application of top coating: 300 g of lanthanum aluminum composite oxide and 700 g of second cerium zirconium composite oxide were weighed in a mass ratio of 3:7, wherein the second cerium zirconium composite oxide comprises ZrO2, CeO2 and Y2O3 in a ratio of 20:70:5. Then, the lanthanum aluminum composite oxide and the second cerium zirconium composite oxide were added into deionized water and stirred evenly to obtain a second slurry. 10 g of rhodium nitrate solution (containing 1 g of Rh element) was added dropwise into the second slurry and stirred evenly to obtain an intermediate coating slurry. Then, the intermediate coating slurry was applied to the semi-finished product obtained in step (1) at a coating amount of 70 g / L. Finally, the catalyst was dried and calcined to obtain a finished product. The drying temperature was 120°C and the drying time was 5 h. The calcination temperature was 550°C and the calcination time was 2 h.

[0064] Emission comparison test:

[0065] The catalyst samples prepared in Examples 1-3 and Comparative Examples 1-3 were aged for 20 h under the same conditions in a high-temperature muffle furnace at 1050° C., and then packaged into a purifier. The whole vehicle emission test was performed according to the WLTC cycle. The engine displacement of the test vehicle was 1.6L. The emission test results are shown in Table 1, where THC represents the total amount of hydrocarbons contained in the gas.

[0066] Table 1

[0067]

[0068] From the comparison results of Examples 1-3 and Comparative Examples 1-3 in Table 1, it can be concluded that, compared with the catalyst of Comparative Examples 1-3, the catalyst of Examples 1-3 reduces the exhaust emission concentration after aging, indicating that the catalyst prepared by the embodiments of the present invention has excellent exhaust gas purification ability and high durability, and exhibits good catalytic performance for both THC and CO; on the one hand, the catalyst is combined with the precious metal Pd and the MgO-Al2O3 material, and the strong interaction between MgO-Al2O3 and Pd effectively realizes that Pd is more stably anchored on the carrier and more evenly distributed under high temperature conditions, which can effectively accelerate the ignition of the catalyst and ensure the high temperature stability of the catalyst; on the other hand, the outermost layer of the catalyst is impregnated with lanthanum salt to adjust the multi-layer distribution control of La in the catalyst, further improving the anti-sintering performance of the catalyst, so that the catalyst prepared by the present invention has broad application prospects.

[0069] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A three-way catalyst for purifying automobile exhaust gas with resistance to degradation, characterized in that: The invention comprises a carrier and a coating applied on the carrier, wherein the coating comprises a lower coating, an intermediate coating and an upper coating arranged on the carrier in sequence from bottom to top, the lower coating comprises a magnesium-aluminum composite oxide, a first cerium-zirconium composite oxide and a precious metal Pd, the intermediate coating comprises a lanthanum-aluminum composite oxide, a second cerium-zirconium composite oxide and a precious metal Rh, and the upper coating is a lanthanum coating formed by immersing in a lanthanum salt solution.

2. The three-way catalyst for purifying automobile exhaust gas with resistance to degradation according to claim 1, characterized in that: The loading amount of the noble metal Pd in ​​the lower coating is 1-200 g / ft 3 The loading amount of the noble metal Rh in the intermediate coating is 0.1-30 g / ft 3 .

3. The three-way catalyst for purifying automobile exhaust gas with resistance to degradation according to claim 1, characterized in that: In terms of mass percentage, the magnesium-aluminum composite oxide includes 1 wt % to 30 wt % of magnesium oxide and 70 wt % to 99 wt % of aluminum oxide.

4. The three-way catalyst for purifying automobile exhaust gas with resistance to degradation according to claim 1, characterized in that: In terms of mass percentage, the first cerium-zirconium composite oxide and the second cerium-zirconium composite oxide both include 4wt% to 79wt% ZrO2, 20wt% to 95wt% CeO2 and 1wt% to 10wt% transition metal oxide, wherein the transition metal oxide is selected from La2O3, Y2O3, Pr6O 11 , one or more of Nd2O3.

5. The three-way catalyst for purifying automobile exhaust gas with resistance to degradation according to claim 1, characterized in that: The mass ratio of the magnesium-aluminum composite oxide to the first cerium-zirconium composite oxide is 1:10-10:

1.

6. The three-way catalyst for purifying automobile exhaust gas with resistance to degradation according to claim 1, characterized in that: In terms of mass percentage, the lanthanum-aluminum composite oxide includes 1wt%-10wt% of lanthanum oxide and 90wt%-99wt% of aluminum oxide.

7. The three-way catalyst for purifying automobile exhaust gas with resistance to degradation according to claim 1, characterized in that: The mass ratio of the lanthanum aluminum composite oxide to the second cerium zirconium composite oxide is 1:10-10:

1.

8. The method for preparing the three-way catalyst for purifying automobile exhaust gas with resistance to degradation according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) coating of the lower coating layer: weighing a magnesium aluminum composite oxide and a first cerium zirconium composite oxide in a mass ratio of 1:10 to 10:1, then adding the magnesium aluminum composite oxide and the first cerium zirconium composite oxide into deionized water and stirring them uniformly to obtain a first slurry, adding a precious metal Pd precursor solution dropwise into the first slurry, then stirring uniformly to obtain an undercoat layer slurry, then coating the undercoat layer slurry on a carrier at a coating amount of 50 to 200 g / L, and finally drying and calcining to obtain a first semi-finished product; (2) Application of intermediate coating: weighing lanthanum aluminum composite oxide and second cerium zirconium composite oxide in a mass ratio of 1:10 to 10:1, then adding the lanthanum aluminum composite oxide and the second cerium zirconium composite oxide into deionized water and stirring evenly to obtain a second slurry, adding a precursor solution of precious metal Rh dropwise into the second slurry, stirring evenly to obtain an intermediate coating slurry, then applying the intermediate coating slurry at a coating amount of 50 to 200 g / L onto the semi-finished product obtained in step (1), and finally drying and calcining to obtain a second semi-finished product; (3) Coating of the top coating: impregnate a certain amount of lanthanum salt solution from the air inlet end onto the second semi-finished product prepared in step (2), control the impregnation height to be 80% to 90% of the catalyst length, and finally dry and calcine to obtain a finished catalyst.

9. The method for preparing the three-way catalyst for purifying automobile exhaust gas with resistance to degradation according to claim 8, characterized in that: In step (1), step (2) and step (3), the drying temperature is 80-200° C., the drying time is 0.1-10 h, the roasting temperature is 450-800° C., and the roasting time is 1-8 h.

10. The method for preparing the three-way catalyst for purifying automobile exhaust gas with resistance to degradation according to claim 8, characterized in that: In step (3), the lanthanum salt is selected from one or more of lanthanum nitrate, lanthanum acetate, and lanthanum aminosulfonate, and the impregnation amount of the lanthanum salt solution is 0.1-10 g / L.

Citation Information

Cited By

  • Deterioration-resistant automobile exhaust purification three-way catalyst and preparation method thereof

    CN122006692A